Peranan Akuntan Publik Pada Pasar Modal Syariah - Suhadi, Suhadi (BISNIS, 2015)
The development of the capital market shari’a implicated in the demandsof stakeholders on the role of the public accountant in order to produce a reportaudited financial maximum more. Of course this is not an excessive, because itwants the real financial information and avoid the asymmetry of information. Inthe audit of course there are some differences with the conventional accountingreport because in Islamic capital market report using the earlier shari’a. In thisSharia PSAK development is done with general PSAK but psak model is basedon the shari’a with reference fatwa MUI. PSAK Shari’a is located in the PSAK100-106 which consists of the conceptual framework presentation of shariafinancial report, accounting murabahah, musyarakah, mudharabah, greeting,and istishna. Public Accountant on capital market shari’a course is required topay attention to the aspects of that is on the value of Islam.